Pengaruh Brand Image Dan Gaya Hidup Hedonis Terhadap Keputusan Pembelian Iphone Di Kota Surabaya - Fitria, Ariyana (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This research aims to discover and analysis the impact of brand image and hedonism lifestyle on iPhone buying decisions. The independent variables of this research are Hedonism lifestyle (X1) and Brand Image (X2), whereas the dependent variable of this research is Purchasing Decision (Y). The research samples were 100 people with the sampling technique used was non-probability sampling. Data processing was carried out using SPSS 18 for Windows computer software. The data analysis technique used in this research was done with Multiple Linear Regression. The research results indicated that Brand Image and Hedonism Lifestyle significantly affects iPhone purchasing decisions in Surabaya. With this research, it is hoped that people can be more observant in determining purchasing decisions, including how to make lifestyle and brand image a consideration in purchasing decisions.